Comparison of human computer interaction on Windows and Linux operations systems - Viduka Dejan; Kraguljac Vladimir M. (Trendovi u Poslovanju)
We have done a comparative analysis between the Microsoft Windows and Linux graphical environment. We are witnesses of a long discussions about their applicability and superiority in the IT world. One of the main obstacles to the wider use of Linux is just a habit of using existing tools and interfaces which users have contact with. In the paper we have presented the Microsoft Windows and Linux graphical interfaces, in scope of their similarities and differences.